AN INVESTIGATION ON THE TREATMENT OF TANNERY WASTEWATER BY ELECTROCOAGULATION - Apaydin, Oe.; Kurt, U.; Gonullu, M. T. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2009)
Treatability by the electro-coagulation (EC) and electro-Fenton (EF) methods have been applied to the tannery wastewater from an organized industrial region consisting mostly of tannery plants and compared with each other in this study. Iron plates were used as the anode and cathode. Electrical current was applied at a value of 33.3 mA m(-2) for all processes in order to determine the electricity consumptions for chemical oxygen demand (COD) and sulfide removal. The optimal contact duration for each process was discovered at the end of the first five minutes. During the EC process, the removal efficiencies of COD and sulfide were 46% and 90%, respectively. Electricity consumptions were also obtained as 1.8 kWh kg(-1) COD removed and 27.7 kWh kg(-1) sulfide removed. During the EF process, on the other hand, the removal efficiencies of COD and sulfide parameters were 54% and 85%, respectively, and electricity consumptions were also obtained as 1.5 kWh kg(-1) COD removed and 8.3 kWh kg(-1) sulfide removed. Furthermore, the removal efficiencies of total Chrome and suspended solids were determined to be 97% and 70%, respectively.
Keywords: Electrocoagulation; Electrofenton; Chrome; Electricity consumption; Iron electrode; Tannery wastewater treatment; ELECTROCHEMICAL OXIDATION; LANDFILL LEACHATE; ANODIC-OXIDATION; EFFLUENTS; FENTON; Environmental Sciences & Ecology